PERISCOPE: road towards effective control of pertussis. Issue 5 (May 2019) - ; Diavatopoulos, Dimitri A.; Mills, Kingston H.G.; Kester, Kent E.; Kampmann, Beate; Silerova, Marcela; Heininger, Ulrich; van Dongen, Jacques J.M.; van der Most, Robbert G.; Huijnen, Martijn A.; Siena, Emilio; Mielcarek, Nathalie; et al.
Summary: The resurgence and changing epidemiology of pertussis in high-income countries, the high infant mortality caused by pertussis in low-income countries, and the increasing morbidity in all age groups worldwide call for a concerted effort to both improve the current vaccines and develop new vaccines and vaccination strategies against pertussis. In this Personal View, we identify several key obstacles on the path to developing a durable solution for global control of pertussis. To systematically address these obstacles, the PERtussIS Correlates Of Protection Europe (PERISCOPE) Consortium was established in March, 2016. The objectives of this consortium are to increase scientific understanding of immunity to pertussis in humans induced by vaccines and infections, to identify biomarkers of protective immunity, and to generate technologies and infrastructure for the future development of improved pertussis vaccines. By working towards the accelerated licensure and implementation of novel, well tolerated, and effective pertussis vaccines, we hope to strengthen and stimulate further collaboration and transparency between the key stakeholders, including the public, the scientific community, public health institutes, regulatory authorities, and vaccine manufacturers.